Targeted harassment, subcultural identity and the embrace of difference: a case study - Hodkinson, Paul (The British journal of sociology, 2019)
This paper examines the significance of experiences and understandings of targeted harassment to the identities of youth subcultural participants, through case study research on goths. It does so against a context of considerable recent public discussion about the victimization of alternative subcultures and a surprising scarcity of academic research on the subject. The analysis presented indicates that, although individual direct experiences are diverse, the spectre of harassment can form an ever‐present accompaniment to subcultural life, even for those who have never been seriously targeted. As such, it forms part of what it is to be a subcultural participant and comprises significant common ground with other members. Drawing upon classic and more recent understandings of how subcultural groups respond to broader forms of outside hostility, we show how the shared experience of feeling targeted for harassment tied in with a broader subcultural discourse of being stigmatized by a perceived ‘normal’ society. The role of harassment as part of this, we argue, contributed to the strength with which subcultural identities were felt and to a positive embrace of otherness.